Bhagavāna Śrī Svāminārāyaṇa : aksharādhipati pūrṇa purushottamanārāyaṇa Śrī Sahajānanda Svāmī - Dave, Harshadarāya Tribhuvanadāsa, 1913- (Svāminārāyaṇa sāhitya granthamāḷā, 1979)
Biography of Swami Sahajānanda, 1781-1830, founder of the Swami-Narayanis, Vaishnavite sect in Hinduism.